The application of a C* flight control law to large civil transport aircraft - Field, Edmund (Cranfield University, 1993)
The work contained in this report is part of an on-going programme of research into handling qualities of fly-by-wire civil transport aircraft currently being undertaken within the Flight Dynamics Group of the College of Aeronautics . Although much work has been undertaken into handling qualities of military aircraft over the last 30 years, civil aircraft have received considerably less attention. Over the last decade civil transport aircraft incorporating fly-by-wire flight control systems have been introduced into commercial operation, the latest including some modified aerodynamic designs. However the civil arena lacks the supporting research into handling qualities that the military side has enjoyed. More recently the civil side is beginning to receive the attention it deserves with work in Europe by Fokker and the Group for Aeronautical Research and Technology in EURope (GARTEUR), for example. In the United States much work has been done by the manufacturers such as Boeing and McDonnell Douglas, and as ever work supported by the US Air Force and NASA. The primary aim of this current programme is to design flight control laws to give fly-by-wire civil transport aircraft excellent flying qualities at all flight conditions, but especially in piloted flight phases. The most critical flight phase of a civil transport is that of the landing approach, and, as with other studies of this type, this phase receives the greatest attention in this study. This report concerns an analysis of the C* parameter. The C* criterion was one of the first handling qualities criteria designed to take account of advanced aerodynamic designs of modern aircraft and higher order systems introduced by flight control systems. Several aircraft have since employed control laws based around the C* parameter. A proportional feedback C* controller was applied to a Boeing 747-100 in landing approach configuration, and assessed against the C* criterion and the US military specification MIL-STD- 1797A.

This report is an ex5ension of the work carried out in [16]. In [16] we defined arbitrary-order numerical methods for model scalar hyperbolic equation. In this report we extended these methods to linear hyperbolic systems where waves can propagate in both directions. First, we define a generalized numerical formula which can accommodate arbitrary wave speeds for scalar advection equation. Then to illustrate its application, we derive three, four, and five point generalized numerical schemes. Finally, according to the theory of linear systems, we extend the generalized schemes to linear hyperbolic systems in a straight forward manner.